Increased drought reduces acorn production in Quercus ilex coppices: thinning mitigates this effect but only in the short term - Sánchez-Humanes, Belén; Espelta, Josep Maria (Forestry, 2011)
In order to explore the effects of climate change on Mediterranean regenerating forests, we experimentally assessed the effects of increased drought on the reproductive attributes of Quercus ilex over a 4-year period (2005–2008). We also investigated whether traditional thinning (selection of one to a few stems per stump) could mitigate the consequences of increased drought in oak coppices. Increased drought reduced the number of reproductive trees, mean number of female flowers produced and acorn crop size, although most of these effects appeared only in the last 2 years of the experiment. In a different way, thinning enhanced all reproductive attributes, but its main effects were transient and covered only 1 or 2 years after the application of the treatments. Our results indicate that a moderate reduction in rainfall (15 per cent) reduces the reproductive ability of Q. ilex. This may have long-term negative consequences for recruitment as well as for the fauna feeding on acorns. Although traditional thinning may mitigate the consequences of increased drought, it has a remarkably short-term effect. This highlights the need to re-examine traditional forestry practices as potential adaptive strategies for coping with climate change in Mediterranean regenerating forests.
10.1093/forestry/cpq04510.1093/forestry/cpq045
Keywords: acorn production; Drought; Mediterranean forest (voyant); Quercus ilex; thinning

Pre-dispersal acorn predation in mixed oak forests: interspecific differences are driven by the interplay among seed phenology, seed size and predator size - ESPELTA, JOSEP M.; Bonal, Raul; Sánchez-Humanes, Belén (Journal of Ecology, 2009)
1. Pre-dispersal seed predation (PSP) often occurs in multi-host–predator systems (e.g. several plant species exposed to a common array of granivorous insects). However, whether the interaction among seed phenology, seed size and predator size accounts for interspecific differences in PSP remains elusive. 2. We studied PSP in a mixed-oak forest with two oaks (the larger-seeded Quercus humilis and the smaller-seeded Q. ilex), both depredated by two acorn weevils (the smaller Curculio glandium and the larger C. elephas). We intensively monitored acorn production and infestation phenology and we identified the weevil species depredating acorns by means of DNA taxonomy. 3. The minimum acorn size required for infestation was lower for C. glandium than for C. elephas, in accordance with their different body sizes. This resulted in an earlier infestation phenology in C. glandium and the ability of this species to infest both smaller and larger acorns. Above a minimum acorn size threshold, no selection for larger acorns by weevils was observed. 4. Initial acorn crop size was similar in the two oaks. Nonetheless, the earlier acorn phenology and the production of larger acorns in Q. humilis favoured the earlier infestation by C. glandium and the predation by both small and large weevils. Smaller acorns of Q. ilex almost excluded infestation by the larger C. elephas. 5. Although larger acorns of Q. humilis could better survive infestation (preserve the embryo), higher PSP in this species finally resulted in a lower mature acorn crop size than in Q. ilex. 6. Synthesis. In a multi-host–predator system, smaller-seeded species may benefit from a reduced PSP because they exclude larger granivorous insects, but also by means of a ‘free-rider effect’, if larger-seeded heterospecifics earlier reach a critical size to be depredated. These results also highlight the benefits of a small body size in granivorous insects to depredate seeds earlier and to forage on a wider range of seed sizes. Whether the advantage of ‘being small’ in this antagonistic plant–animal interaction is offset by other processes, or whether it results in a pressure towards seed and insect size reduction, deserves further attention.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Curculio elephas; Curculio glandium; Mediterranean oak forests; multi-host–predator system; Quercus humilis; Quercus ilex; seed ecology; seed satiation; species coexistence

Pre-dispersal acorn predation in mixed oak forests: interspecific differences are driven by the interplay among seed phenology, seed size and predator size - Espelta, Josep M; Bonal, Raul; Sánchez-Humanes, Belén (Journal of Ecology, 2009)
1. Pre-dispersal seed predation (PSP) often occurs in multi-host–predator systems (e.g. several plant species exposed to a common array of granivorous insects). However, whether the interaction among seed phenology, seed size and predator size accounts for interspecific differences in PSP remains elusive. 2. We studied PSP in a mixed-oak forest with two oaks (the larger-seeded Quercus humilis and the smaller-seeded Q. ilex), both depredated by two acorn weevils (the smaller Curculio glandium and the larger C. elephas). We intensively monitored acorn production and infestation phenology and we identified the weevil species depredating acorns by means of DNA taxonomy. 3. The minimum acorn size required for infestation was lower for C. glandium than for C. elephas, in accordance with their different body sizes. This resulted in an earlier infestation phenology in C. glandium and the ability of this species to infest both smaller and larger acorns. Above a minimum acorn size threshold, no selection for larger acorns by weevils was observed. 4. Initial acorn crop size was similar in the two oaks. Nonetheless, the earlier acorn phenology and the production of larger acorns in Q. humilis favoured the earlier infestation by C. glandium and the predation by both small and large weevils. Smaller acorns of Q. ilex almost excluded infestation by the larger C. elephas. 5. Although larger acorns of Q. humilis could better survive infestation (preserve the embryo), higher PSP in this species finally resulted in a lower mature acorn crop size than in Q. ilex. 6. Synthesis. In a multi-host–predator system, smaller-seeded species may benefit from a reduced PSP because they exclude larger granivorous insects, but also by means of a ‘free-rider effect’, if larger-seeded heterospecifics earlier reach a critical size to be depredated. These results also highlight the benefits of a small body size in granivorous insects to depredate seeds earlier and to forage on a wider range of seed sizes. Whether the advantage of ‘being small’ in this antagonistic plant–animal interaction is offset by other processes, or whether it results in a pressure towards seed and insect size reduction, deserves further attention.
Keywords: Curculio elephas; Curculio glandium; Mediterranean oak forests; multi-host–predator system; Quercus humilis; Quercus ilex; seed ecology; seed satiation; species coexistence

Masting mediated by summer drought reduces acorn predation in mediterranean oak forests - Espelta, Josep Maria; Cortés, Pilar; Molowny-Horas, Roberto; Sánchez-Humanes, Belén; Retana, Javier (ECOLOGY, 2008)
Temporally variable production of seed crops by perennial plants (masting) has been hypothesized to be a valuable mechanism in the reduction of seed predation by satiating and starving seed consumers. To achieve these benefits, coexisting species subjected to the same predator would benefit from a similar pattern of seeding fluctuation over time that could lead to a reduction in predation at the within-species level. We tested for the existence of an environmental factor enforcing synchrony in acorn production in two sympatric Mediterranean oaks ( Quercus ilex and Q. humilis) and the consequences on within-species and between species acorn predation, by monitoring 15 mixed forests (450 trees) over seven years. Acorn production in Q. ilex and Q. humilis was highly variable among years, with high population variability (CVp) values. The two species exhibited a very different pattern across years in their initial acorn crop size ( sum of aborted, depredated, and sound acorns). Nevertheless, interannual differences in summer water stress modified the likelihood of abortion during acorn ripening and enforced within-and, particularly, between-species synchrony and population variability in acorn production. The increase in CVp from initial to mature acorn crop ( after summer) accounted for 33% in Q. ilex, 59% in Q. humilis, and 60% in the two species together. Mean yearly acorn pre-dispersal predation by invertebrates was considerably higher in Q. humilis than in Q. ilex. Satiation and starvation of predators was recorded for the two oaks, and this effect was increased by the year-to-year variability in the size of the acorn crop of the two species combined. Moreover, at a longer time scale ( over seven years), we observed a significant reduction in the mean proportion of acorns depredated for each oak and the variability in both species' acorn production combined. Therefore, our results demonstrate that similar patterns of seeding fluctuation over time in coexisting species mediated by an environmental cue ( summer drought) may contribute to the reduction of the impact of seed predation at a within-species level. Future research should be aimed at addressing whether this process could be a factor assisting in the coexistence of Q. ilex and Q. humilis.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: Curculio spp.; fruit abortion; fruiting synchrony; Mediterranean mixed-oak forests; oaks; predator satiation; Quercus humilis; Quercus ilex; resource matching

Masting mediated by summer drought reduces acorn predation in mediterranean oak forests - Espelta, Josep Maria; Cortés, Pilar; Molowny-Horas, Roberto; Sánchez-Humanes, Belén; Retana, Javier (ECOLOGY, 2008)
Temporally variable production of seed crops by perennial plants (masting) has been hypothesized to be a valuable mechanism in the reduction of seed predation by satiating and starving seed consumers. To achieve these benefits, coexisting species subjected to the same predator would benefit from a similar pattern of seeding fluctuation over time that could lead to a reduction in predation at the within-species level. We tested for the existence of an environmental factor enforcing synchrony in acorn production in two sympatric Mediterranean oaks ( Quercus ilex and Q. humilis) and the consequences on within-species and between species acorn predation, by monitoring 15 mixed forests (450 trees) over seven years. Acorn production in Q. ilex and Q. humilis was highly variable among years, with high population variability (CVp) values. The two species exhibited a very different pattern across years in their initial acorn crop size ( sum of aborted, depredated, and sound acorns). Nevertheless, interannual differences in summer water stress modified the likelihood of abortion during acorn ripening and enforced within-and, particularly, between-species synchrony and population variability in acorn production. The increase in CVp from initial to mature acorn crop ( after summer) accounted for 33% in Q. ilex, 59% in Q. humilis, and 60% in the two species together. Mean yearly acorn pre-dispersal predation by invertebrates was considerably higher in Q. humilis than in Q. ilex. Satiation and starvation of predators was recorded for the two oaks, and this effect was increased by the year-to-year variability in the size of the acorn crop of the two species combined. Moreover, at a longer time scale ( over seven years), we observed a significant reduction in the mean proportion of acorns depredated for each oak and the variability in both species' acorn production combined. Therefore, our results demonstrate that similar patterns of seeding fluctuation over time in coexisting species mediated by an environmental cue ( summer drought) may contribute to the reduction of the impact of seed predation at a within-species level. Future research should be aimed at addressing whether this process could be a factor assisting in the coexistence of Q. ilex and Q. humilis.
Keywords: Curculio spp.; fruit abortion; fruiting synchrony; Mediterranean mixed-oak forests; oaks; predator satiation; Quercus humilis; Quercus ilex; resource matching